A Literature Review and Case Report on Thoracic Outlet Syndrome - Jurgutavičius, Povilas; Minderis, Mindaugas (Lietuvos chirurgija, 2025)
Thoracic outlet syndrome (TOS) is a clinical entity comprising a constellation of symptoms resulting from compression of the neurovascular bundle in the thoracic outlet. Vascular, neurological, and neurovascular types of TOS are distinguished according to the structures affected. The most common form of TOS is neurological, occurring in up to 95% of cases. TOS is a common neurological disease with a wide range of symptoms. It is still little known to medical professionals and is often undiagnosed or diagnosed late.This study provides a literature review of the symptomatology and treatment methods for TOS, highlighting certain symptoms not previously documented in the literature and presenting an illustrative clinical case. A 67-year-old female reported left arm pain following a muscle biopsy conducted for suspected polymyositis. The pain radiated to the inner arm, shoulder blade, and distal parts of the arm. The patient had been experiencing chronic facial and head pain, as well as nausea, for 35 years. Examination revealed arm weakness and positive thoracic outlet syndrome (TOS) provocation tests. Brachial plexus decompression were performed, resulting in an excellent treatment outcome.This case highlights the complexity of TOS presentations and the importance of considering TOS in differential diagnoses.
Keywords: thoracic outlet syndrome; neurological thoracic outlet syndrome; brachial plexus compression; scalenotomy